Ogbanje/abiku and cultural conceptualizations of psychopathology in Nigeria - Ilechukwu, Sunday T. C. (Mental health, religion & culture, 2007)
Ogbanje/abiku refer to people who are believed to cycle rapidly and repeatedly through birth and death. A consecutive familial sequence of births and deaths of infants is construed as the same child dying and being born over and over again. The Igbos believe that ogbanje results from subversion of human destiny by willful alliance of the newborn with deities who guard the postulated interface between birth and pre-birth (spirit) existence, while the Yoruba attribute many abiku to possession of a pregnancy by spirit pranksters most often referred to as emere. Surviving persons manifest abnormalities of psychological life with vivid fantasy life or dreams characterized by the presence of water, orgiastic play with unfamiliar children, and frightening contact with a water goddess—mammy water. Labeled children and adolescents often exhibit manipulative, histrionic dissociative, and other maladaptive behavior. They may also be gifted. Contradictory and facultative practices of excessive indulgence of and ostentatious hostility towards ogbanje/abiku children are described but are better understood as exhibitions of acceptance of life and rejection of death. This paper reports one study of the deployment of cultural cosmology in shaping individual and group adaptive responses to high infant mortality in Nigeria.